Beauveria Bassiana; Insect Pathogen And Biopesticide Producer As An Effective And Environmentally Friendly Alternative For Biological Control - Hadiyanto; Eko Wahjono, Tri; Yuliani, Yeni (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2024)
Beauveria bassiana is one of the insect pathogens that can be used as a biological control agent. The interaction between Beauveria bassiana and other natural enemies in biological control can affect the effectiveness of pest control as a biopesticide. The efficacy of these fungi was also influenced by the toxin produced (beauvericin, bassianin, bassiacridin, beauvericin, bassianolide, cyclosporine, oosporein, and tenellin) which may interfere the nervous system and kill the target insects. The use of chemical pesticides, which has been one of the farmers’ choices in pest control, has negative impacts on the environment, human health, and pest resistance therefore, B. bassiana as an alternative, biological pest control and biological control are increasingly considered as environmentally friendly and sustainable control methods, so that biological control can become an important alternative to reduce the use of chemical pesticides. Facing this problem, alternative methods including the use of entomopathogenic fungi as biopesticide could be a sound measure to preserve the environment, biodiversity and ensure good quality of crops.